Graphene Nanocylinders: Hybridized Radial and Edge Coupled 3D Plasmon Modes in Self‐Assembled Graphene Nanocylinders (Small 14/2021). Issue 14 (8th April 2021) - Dai, Chunhui; Agarwal, Kriti; Bechtel, Hans A.; Liu, Chao; Joung, Daeha; Nemilentsau, Andrei; Su, Qun; Low, Tony; Koester, Steven J.; Cho, Jeong‐Hyun
Abstract : In article number 2100079, Jeong‐Hyun Cho and co‐workers report hybridized 3D plasmon modes stemming from 3D graphene nanostructures, resulting in non‐surface‐limited (volumetric) field enhancements and a four orders of magnitude stronger field at the openings of cylinders than in rectangular 2D graphene ribbons.